Peopling Culture with the Performance of the Forest:: the life of viadoplants and the trans-species scene - Leal, Dodi; Moura Farias, Saile (Revista Brasileira de Estudos da Presença, 2023)
The text addresses the performance of the forest as a paradigm of cultural peopling that breaks with the totalizing notions of humanity-urbanity present in colonial sex-gender hegemonies. The core of the work is the bodily figures viadoplants and trans-species as vegetative ways of inclining life and the scene. Based on the lines of strength of the work Corpoflor and the conception of corpoluz developed in the work TRAVED: palestra-performance em realidade virtual, the study articulates ethical-philosophical paradigms of peopling of culture, thus recognizing forests as sexualized and gendered performative entities.